Intertextuality in Nusantara Qur’anic Exegesis: A Study of Tafsīr al-Itqān fī Ma’ānī Umm al-Qur’ān by KH. Ahmad Haris Shadaqah - Hadani, Abdullah; Bakar, Abu; Kholid, Abd. (Program Studi Ilmu Al-Qur'an dan Tafsir Fakultas Ushuluddin dan Filsafat, UIN Ar-Raniry, 2024)
This article analyzes the intertextual characteristics of Tafsīr al-Itqān fī Ma’ānī Umm al-Qur’ān by KH. Ahmad Haris Shadaqah, a prominent Nusantara scholar. The study examines how Shadaqah extensively integrates classical texts, such as Ḥashiyah al-Ṣāwi ‘ala al-Jalālayn, Marāh Labīd al-Nawāwi, Tafsīr Ibn Kathīr, Anwār al-Tanzīl Wa Asrār al-Ta’wīl, and Mafātīḥ al-Ghayb, as well as Matn al-Ḥikam and Syarḥ al-Ḥikam, to produce a Javanese-language tafsir. Employing Julia Kristeva’s theory of intertextuality, this qualitative study combines literature review and fieldwork to identify intertextual patterns, including transformation, modification, haplology, expansion, and existence. The findings reveal that Shadaqah’s tafsir bridges classical Islamic thought and local cultural contexts, emphasizing the significance of local languages in the development of Qur’anic exegesis. This research highlights the adaptability of Islamic scholarly traditions in addressing contemporary and regional needs, contributing to the broader discourse on intertextuality and Qur’anic studies.